Infrastructure Aid, Deindustrialization, and Welfare - Choi, Eun (IMF Working Papers; Working Paper ;, 2005)
This paper investigates the deindustrialization and welfare effects of infrastructure aid in developing countries. In the short run, cost-saving infrastructure aid in the export sector increases the domestic wage rate, whereas the same aid in the import sector lowers it. The cost of nontraded goods rises whether the export or the import sector receives infrastructure aid. Infrastructure aid in the nontraded sector has no effect on domestic factor prices. Laborsaving infrastructure aid causes an expansion of the export sector, while capital-saving infrastructure aid results in a Dutch disease effect in the export sector. If aid is below the optimal level, infrastructure aid increases consumer income and welfare.